Decorating Phosphorus‐Doped g‐C3N4 with Zinc Porphyrin Metal–Organic Framework via an Electrostatic Self‐Assembly Process: An Efficient Strategy to Boost Photocatalytic Hydrogen Evolution Performance. Issue 12 (9th October 2022) - Ma, Dandan; Shi, Jian-Wen; Pu, Zengxin; Mao, Siman; Xu, Xuan; He, Dan; Guo, Rui; Chen, Feng
Abstract : Herein, a novel 2D/2D heterostructure, phosphorus‐doped carbon nitride nanosheet/zinc porphyrin metal–organic framework (MOF) (HPCNN/ZnPMOF), is elaborately fabricated through an electrostatic self‐assembly process for photocatalytic H2 evolution from water splitting. The as‐prepared HPCNN/ZnPMOF 2D/2D photocatalyst displays the highest H2 evolution rate of 65.3 mmol g −1 h −1 under simulated solar irradiation, which is 2.2 and 49.1 times higher than that of HPCNN and ZnPMOF, respectively. The enhanced photocatalytic activity can be ascribed to the intimate contact interface and the shortened migration distance formed by the unique 2D/2D structure, resulting in dramatically enhanced separation and transfer efficiencies of hole–electron pairs. Furthermore, P doping endows carbon nitride with more separation sites of photoinduced charge carriers and consequently establishes type‐II heterojunction with ZnPMOF. This work shed lights on the potential of designing the highly efficient MOF/g‐C3 N4 2D/2D system for water splitting H2 evolution. Abstract : The 2D metal–organic framework and phosphorus‐doped 2D g‐C3 N4 nanosheets are tightly coupled by an electrostatic self‐assembly strategy to form a 2D/2D heterostructure, where the type II transfer mechanism of photoinduced charge carriers is established, significantly boosting photocatalytic hydrogen evolution performance.